치위생과 학생의 2×2 성취목표지향성이 자기조절학습에 미치는 영향 - 최규일; Gyu Yil Choi; 정기옥; Gi Ok Jung (Chiwisaeng gwahakoeji, 2012)
This research will target the Dental Hygienics students to identify the level and type of the 2×2 achievement target orientation, and will study how this achievement target orientation is related to the Self-Regulated Learning, as well as the effect on the each sub elements of the Self-Regulated Learning (SRL). Among the 2×2 achievement target orientation of all the female university students, the skillful approach was found to be highest. In case of the adjustment of the motivation following grade, intrinsic value of the 1st grader was higher than the intrinsic value of the 2nd and 3rd graders. As for the behavior adjustment, the 3rd grader`s time and studying adjustment were found to be higher. Mean while, pursuit of the cooperation was found to be high compared to the time and studying adjustment of the1st and 2nd graders. Second, intrinsic value, overt goal orientation, and studying environment adjustment among the SRL`s subelements, manifested significant correlation with all the sub elements of the 2×2 achievement target orientation. As for the elements that affected cognition adjustment, grade and skillful approach were found to exert significant effect on the performance adjustment. As for the element that affects behavior adjustment, grade and skillful approach exerted significant effect on the sub elements of the behavior adjustment. Analysis on the effect of the achievement target orientation and SRL implies that the direction of the students` learning goal can be modified and that they can learn effectively by using the SRL appropriately. When the two elements are factored in carefully, the key findings could serve as a base data that can motivate the students, inducing effective learning process.